The Gospels : A Vault on the Life of Jesus Christ - Whitman Publishing (Virginia : Whitman Publishing, 2010)
The Gospel Vault: The Life of Jesus Christ features the story of His extraordinary ministry not only through the holy scriptures of Matthew, Mark, Luke and John, but through centuries of artistic depictions of the Savior's life. Selected events of Christ's childhood, ministry, death and resurrection are lavishly illustrated with a rich pallet of artistic media that spans over 2,000 years. Paintings, sculptures, drawings, etchings, textiles, carvings and mosaics from the ancient to the modern are woven together to create a breathtaking overview of His life. Many of the artworks found in this book are famous, but there are also numerous and fascinating pieces of art from some of the world's lesser-known collections. The text, presented alongside actual scripture, provides an easy-to-understand framework for a deeper insight into the events depicted on the pages, the artists represented and the historical backdrop against which the art was created.
Keywords: New Testament Gospels -- Non-fiction